2011
DOI: 10.1016/j.str.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

RNA Tertiary Interactions in a Riboswitch Stabilize the Structure of a Kink Turn

Abstract: SummaryThe kink turn is a widespread RNA motif that introduces an acute kink into the axis of duplex RNA, typically comprising a bulge followed by a G⋅A and A⋅G pairs. The kinked conformation is stabilized by metal ions, or the binding of proteins including L7Ae. We now demonstrate a third mechanism for the stabilization of k-turn structure, involving tertiary interactions within a larger RNA structure. The SAM-I riboswitch contains an essential standard k-turn sequence that kinks a helix so that its terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 33 publications
5
83
2
Order By: Relevance
“…23 In agreement with this model, it was previously found that the folding of the kink-turn motif located in the P2 helical domain is crucial for the structure and ligand binding activity of the SAM-I aptamer. 46,50 Our study also revealed that SAM binding to the aptamer produces a second folding transition involving the stacking of stems P1 and P4. 23 SAM binding was also previously shown to reorganize regions J1/2 and J3/4, 33,54 consistent with the formation of the native RNA-ligand complex as observed in the crystal structure.…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 51%
See 1 more Smart Citation
“…23 In agreement with this model, it was previously found that the folding of the kink-turn motif located in the P2 helical domain is crucial for the structure and ligand binding activity of the SAM-I aptamer. 46,50 Our study also revealed that SAM binding to the aptamer produces a second folding transition involving the stacking of stems P1 and P4. 23 SAM binding was also previously shown to reorganize regions J1/2 and J3/4, 33,54 consistent with the formation of the native RNA-ligand complex as observed in the crystal structure.…”
Section: S-adenosylmethionine (Sam) Riboswitchessupporting
confidence: 51%
“…2B). 27,38,49,50 The binding site is constituted by the minor grooves of helices P1 and P3, in which the SAM adenine moiety interacts with a bulge located in the P3 stem. The methionine group of the ligand is involved in interactions with the J1/2 region.…”
Section: Folding Of the Sam-i Riboswitchmentioning
confidence: 99%
“…K-turns often mediate long-range interactions in RNAs (Schroeder et al 2011). The increased binding affinity we observed by ITC for VcI-II Kt over VcI-II may reflect promotion of interaptamer ("quaternary") interactions by the Kturn.…”
Section: +mentioning
confidence: 73%
“…The cognate K-turn binding protein YbxF enhances glycine binding to BsI-II Kt K-turns can be stabilized by tertiary structure formation, increased Mg 2+ concentrations, or by K-turn binding proteins (Schroeder et al 2011). To test whether YbxF might improve glycine binding under physiologically relevant Mg 2+ concentrations, we performed ITC as described above with the BsI-II Kt RNA and a 1.5-fold molar excess of B. subtilis YbxF in the sample cell.…”
Section: +mentioning
confidence: 99%
“…The kink-turn motif is not unprecedented in riboswitches; it has been reported in SAM-I riboswitches connecting to the four-way junction motif (Montange and Batey 2006) as well as in the class II c-di-GMP (Lee et al 2010) and lysine riboswitches (Blouin and Lafontaine 2007). This SAM-I kink-turn motif follows the exact consensus derived from the ribosome kink-turns and is stabilized by RNA tertiary structure (Schroeder et al 2011), different from those stabilized by metal ions (Liu and Lilley 2007) or protein binding (Turner et al 2005;Turner and Lilley 2008). It will be interesting to investigate which strategy is used in the glycine riboswitch to stabilize the kinkturn motif located at the 59 boundary of the regulatory RNA element.…”
Section: Discussionmentioning
confidence: 92%